Significance and Challenges of Big Data in Healthcare: A Review - Syed Muhammad Nabeel Mustafa; Hassan Zaki; Syeda Sundus Zehra; Muhammad Shoaib (University of Sindh Journal of Information and Communication Technology, 2022)
The infiltration of information and technology in all the important sectors of the world has influenced the efflux of data. Healthcare industry has greatly benefited more the blessings of advanced computing. This sector is getting digitized at a fast rate for more precision and accuracy. Hence, more data is produced from the healthcare sector. In this review paper, we discuss Big data's importance in the healthcare industry. We go over the qualities of big data, including volume, veracity, speed, variety, and value. The healthcare industry has been touched by big data in practically every way. The diagnosis, telemedicine, medical research, and enhancing patient care are the remaining key effects. The application of Big data gave rise to many challenges such as accuracy, security and privacy, storage and processing, data complexity, unified format, image preprocessing and data analytics. We also intend to investigate further big data uses in healthcare and to highlight the difficulties this industry faces